2017
DOI: 10.1074/jbc.m117.804054
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group RING finger proteins 3/5 activate transcription via an interaction with the pluripotency factor Tex10 in embryonic stem cells

Abstract: Polycomb group (PcG) proteins are epigenetic transcriptional repressors that orchestrate numerous developmental processes and have been implicated in the maintenance of embryonic stem (ES) cell state. More recent evidence suggests that a subset of PcG proteins engages in transcriptional activation in some cellular contexts, but how this property is exerted remains largely unknown. Here, we generated ES cells with single or combined disruption of polycomb group RING finger protein 3 (Pcgf3) and Pcgf5 with the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…Recent studies have suggested that PRC1 and PRC2 can be found associated with actively transcribed genes (Cohen et al, 2018;Frangini et al, 2013;Gao et al, 2014;Stojic et al, 2011;van den Boom et al, 2016;Zhao et al, 2017). We note that in many of those cases, PRC1 and PRC2 complexes appear to act as rheostats to help control (reduce) transcriptional output from active genes, thus in fact still mechanistically acting as repressors (Cohen et al, 2018).…”
Section: Pcg Complexes As Activators?mentioning
confidence: 62%
“…Recent studies have suggested that PRC1 and PRC2 can be found associated with actively transcribed genes (Cohen et al, 2018;Frangini et al, 2013;Gao et al, 2014;Stojic et al, 2011;van den Boom et al, 2016;Zhao et al, 2017). We note that in many of those cases, PRC1 and PRC2 complexes appear to act as rheostats to help control (reduce) transcriptional output from active genes, thus in fact still mechanistically acting as repressors (Cohen et al, 2018).…”
Section: Pcg Complexes As Activators?mentioning
confidence: 62%
“…Previous reports have shown that Pcgf5 is dispensable for mESC self‐renewal by checking cell morphology and expression of core pluripotency markers (Yao et al, 2018; Zhao et al, 2017). In our study, we also did not detect any major morphological changes between Pcgf5 −/− and WT mESCs grown in 2i/L medium.…”
Section: Discussionmentioning
confidence: 99%
“…Using different mESC differentiation strategies, two previous studies have reported inconsistent views about whether loss of Pcgf5 results in the maintenance of primed pluripotency and repression of ectodermal generation (Yao et al, 2018; Zhao et al, 2017). Those conflicting results may be due to the distinct cellular contexts of the respective EB models.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the similar interaction network, but also the regulated gene sets and distinctive function indicate closer connection between the indicated pairs of complexes. For example, PRC1.3-PRC1.5 mainly function as a transcriptional activator in ES cells, promoting the expression of many genes involved in mesoderm differentiation via interaction of TEX10 transcription factor [180]. Only ncPRC1.6 complex provides link to heterochromatin control system, with its HP1 homolog subunits CBX1 and CBX3.…”
Section: Classification Of Mammalian Prc Complexesmentioning
confidence: 99%
“…In recent studies, it was shown that the association of the complexes with the TEX10 transcription factor plays important role in targeting. TEX10 and p300 connection with ncPRC1.3-ncPRC1.5 necessary for promoting the expression of many genes involved in mesoderm differentiation [180].…”
Section: Targeting Of Different Ncprc1 Complexesmentioning
confidence: 99%